TEACH STUDENTS TO THINK LOGICALLY THROUGH DIDACTIC GAMES - HosiyatxonTadjimatova; Husnidaxon Meliyeva (International Engineering Journal For Research & Development, 2020)
This article describes the types, importance and requirements of didactic games.